PENGARUH SUSTAINABILITY DISCLOSURE DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi Shahara; Yulia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of sustainability disclosure on economic, environmental, social, and company size on stock prices. This research is a quantitative research. The research population is manufacturing companies listed on the IDX in 2020-2021, with a total population of 193 companies. The sampling method used is purposive sampling, with this method then obtained as many as 26 research samples. The research data uses secondary data obtained from financial report documentation and sustainability reports published on the Indonesia Stock Exchange web page. Analysis of the data used in the form of multiple linear regression using the SPSS 26 application. The results showed that the sustainability disclosure in the economic and social had no effect on stock prices. Meanwhile, the sustainability disclosure of environment and company size have an effect on stock prices.